2023
DOI: 10.1111/apt.17547
|View full text |Cite
|
Sign up to set email alerts
|

Trends in aetiology‐based hospitalisation for cirrhosis before and during the COVID‐19 pandemic in the United States

Abstract: Summary Background Patients with pre‐existing cirrhosis and COVID‐19 may have a poor prognosis. Aim To evaluate the temporal trends in aetiology‐based hospitalisations and potential predictors of in‐hospital mortality during hospitalisation with cirrhosis before and during the COVID‐19 pandemic. Methods Based on the US National Inpatient Sample 2019–2020, we determined quarterly trends in aetiology‐based hospitalisations with cirrhosis and decompensated cirrhosis, and identified predictors of in‐hospital morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In their recent study, Kim et al, 6 Using a validated case definition for cirrhosis, their study identified an increase in-hospital mortality during the pandemic to 6.6% as compared to 5.6% pre-pandemic. This increase was largely driven by alcohol-related liver disease, that experienced a quarterly percentage increase in hospitalisations of 3.6%.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
See 2 more Smart Citations
“…In their recent study, Kim et al, 6 Using a validated case definition for cirrhosis, their study identified an increase in-hospital mortality during the pandemic to 6.6% as compared to 5.6% pre-pandemic. This increase was largely driven by alcohol-related liver disease, that experienced a quarterly percentage increase in hospitalisations of 3.6%.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…In their recent study, Kim et al, 6 used the US‐based National Inpatient Sample (NIS), a large population‐based dataset, to explore quarterly temporal trends in cirrhosis hospitalisations and mortality based on cirrhosis aetiology from 2019 to 2020 to try and offer further clarity regarding COVID‐19's impact on this population. Using a validated case definition for cirrhosis, their study identified an increase in‐hospital mortality during the pandemic to 6.6% as compared to 5.6% pre‐pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… Increases in rates of admissions for females far higher than for males. Kim et al 2023 16 USA Cross-sectional national database – National Inpatient Sample 316,418 hospitalizations for cirrhosis Hospitalization rates for ALD increased significantly (quarterly percentage change: 3.6%, 95% CI: 2.2–5.1%), with a notably higher rate during the COVID-19 era. COVID-19 era and COVID-19 infection were independent predictors of in-hospital mortality during hospitalization with cirrhosis and decompensated cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Hospitalization rates for ALD-related cirrhosis increased significantly (quarterly percentage change: 3.6%, 95% confidence interval [CI]: 2.2%–5.1%), with a notably higher rate during the COVID-19 era. 16 Liver transplant centers in the United States also manage higher numbers of referrals for severe ALD with recent unhealthy drinking, defined as drinking within the past six months. 17 Concerningly, mortality rates in patients with ALD admitted to hospitals in the United States already appear to be rising.…”
Section: Introductionmentioning
confidence: 99%